Localization of sodium channel subtypes in adult rat skeletal muscle using channel-specific monoclonal antibodies - Haimovich, B (J Neurosci, 1987)
Five monoclonal antibodies specific for the 260 kDa subunit of the rat skeletal muscle sodium channel were used to probe the distribution of this channel in adult muscle. All the antibodies reacted with the surface membrane of fast- and slow-twitch fibers in the rat anterior tibial and soleus muscles. Immunoreactivity was also present in the endplate region; this was significantly more intense than that in the surrounding extrajunctional membrane. At the electron microscopic level, this junctional immunoreactivity could be traced uniformly throughout the secondary folds of the post-synaptic membrane. Three of the monoclonal antibodies (A/B2, F/E4, and I/E3) exhibited an additional distinct immunoreactivity pattern, staining the interior of selected fibers in the anterior tibial muscle that were subsequently identified as slow-twitch fibers. An identical reactivity pattern was observed with most of the soleus muscle fibers. In longitudinal sections of slow fibers examined at the light microscopic level, transversely oriented, regularly spaced doublets of fluorescence were localized at the junction of the A and I bands in each sarcomere. In permeabilized slow fibers exposed to A/B2 and examined at the electron microscopic level, internal reactivity was associated exclusively with the membranes of the T-tubular system. A/B2 also strongly stained a transversely oriented pattern within cardiac muscle fibers exhibiting the characteristics of the T-tubular system in that tissue. We conclude that at least 3 subpopulations of sodium channels are present in adult skeletal muscle: those in the sarcolemma of fast and slow fibers, those in slow-twitch fiber T-tubular membranes, and those in the T-tubular system of fast fibers. The channels in the slow fiber T-system apparently share common epitopes with those in the T-system of cardiac fibers.